A Wilderness Approach under the World Heritage Convention. Issue 3 (2nd November 2015) - Kormos, Cyril F.; Bertzky, Bastian; Jaeger, Tilman; Shi, Yichuan; Badman, Tim; Hilty, Jodi A.; Mackey, Brendan G.; Mittermeier, Russell A.; Locke, Harvey; Osipova, Elena; Watson, James E.M.
Abstract: The World Heritage Convention could make a bigger and more systematic contribution to global wilderness conservation by: (1) ensuring the World Heritage List includes full coverage of Earth's wilderness areas with outstanding universal value and (2) more effectively protecting the ecological integrity of existing World Heritage sites. Here, we assess current coverage of global‐scale wilderness areas within natural World Heritage sites and identify broad gaps where new wilderness sites should be identified for inclusion in the World Heritage List. We also consider how existing mechanisms under the Convention can improve the ecological integrity of existing sites by expanding or buffering them, and by promoting connectivity between World Heritage sites, between World Heritage sites and other protected areas, or both. We suggest that the Convention should consider a new mechanism called a "World Heritage Wilderness Complex" to facilitate a wilderness approach. Finally, we map three landscapes and one seascape to illustrate how World Heritage Wilderness Complexes might be implemented.